Strategi Pemerintah Kabupaten Deli Serdang dalam Implementasi Peraturan Perlindungan Data Pribadi: Studi Kasus di Kecamatan Sibolangit - Jamin Ginting; Ellora Sukardi; Chelsea Surya Roseny; Elisabeth Ryanthie Maya Puteri (Program Studi Kenotariatan Fakultas Hukum Universitas Pelita Harapan, 2026)
This study analyzes the strategy of the Deli Serdang Regency Government in implementing personal data protection regulations, especially in Sibolangit District. In technological developments, the advancement of information technology has increased individual privacy risks, such as identity theft and data leaks. Law Number 27 of 2022 concerning Personal Data Protection (UU PDP) serves as a significant step to protect individual rights in the collection, use, and exchange of personal data. However, implementation at the local level faces challenges. This research uses a qualitative approach with a case study design, involving interviews, observations, and the distribution of questionnaires to 80 respondents from various backgrounds in Sibolangit District. The results show several challenges, such as some community members not fully understanding the UU PDP, a high incidence of data misuse, and a gap between normative awareness and practical caution in managing personal data. Although the public is aware of the importance of data protection, 64 out of 80 respondents are still willing to provide personal data for promotions or certain application registrations. In response, the Deli Serdang Regency Government has implemented strategies that include socializing the dangers of social media use and commercial service registration. The government has also integrated the Satu Data Indonesia program for human resource development and information dissemination through various media. This study recommends the need to strengthen infrastructure, improve human resource capacity, and conduct more targeted education for the public, especially young people and government employees, to be more prudent in managing personal data. Bahasa Indonesia Abstract: Penelitian ini menganalisis strategi Pemerintah Kabupaten Deli Serdang dalam mengimplementasikan peraturan perlindungan data pribadi, khususnya di Kecamatan Sibolangit. Perkembangan digital, kemajuan teknologi informasi telah meningkatkan risiko privasi individu, seperti pencurian identitas dan kebocoran data. Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi (UU PDP) hadir sebagai langkah signifikan untuk melindungi hak-hak individu dalam pengumpulan, penggunaan, dan pertukaran data pribadi. Namun, implementasi di daerah menghadapi tantangan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan wawancara, observasi, dan penyebaran kuesioner kepada 80 responden dari berbagai latar belakang di Kecamatan Sibolangit. Hasil penelitian menunjukkan bahwa terdapat tantangan, seperti sebagian masyarakat yang belum sepenuhnya memahami UU PDP, tingginya insiden penyalahgunaan data, dan adanya celah antara kesadaran normatif dan kehati-hatian praktis dalam mengelola data pribadi. Meskipun masyarakat menyadari pentingnya perlindungan data, 64 dari 80 responden masih bersedia memberikan data pribadi untuk promosi atau pendaftaran aplikasi tertentu. Sebagai respons, Pemerintah Kabupaten Deli Serdang menerapkan strategi yang meliputi sosialisasi bahaya penggunaan media sosial dan pendaftaran layanan komersial. Pemerintah juga telah mengintegrasikan program Satu Data Indonesia untuk pengembangan sumber daya manusia dan diseminasi informasi melalui berbagai media. Penelitian ini merekomendasikan perlunya penguatan infrastruktur, peningkatan kapasitas sumber daya manusia, dan edukasi yang lebih terarah kepada masyarakat, khususnya kaum muda dan pegawai pemerintah, agar lebih bijaksana dalam mengelola data pribadi.